An Investigation into English Idioms Containing the Word “No” and their Vietnamese Equivalents - Phạm Lê Tường Vy (2011)
This thesis attempts to investigate syntactic and semantic features of EIN and their Vietnamese equivalents. The study is carried out through the adoption of descriptive, contrastive, inductive, and deductive methods. The ….